Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.